Early Anti-Corruption Education as an Effort to Create a Corruption-Free Generation - Fata, Ulfa Husnul; Wibisono, Wahyu; Monica, Laily Prima; Ulfa, Maria; Nurmawati, Thatit; Rahmawati, Anita; Arsa, Sandi Alfa Wiga (Journal of Community Service for Health, 2022)
Corruption is a despicable act and a form of social disobedience of society. Corruption always has a bad impact on the life of the nation and state. Anti-corruption education from an early age is one of the powerful pillars in combating the dangers of corruption from an early age. The purpose of this community service program was to initiate anti-corruption values in the community from an early age. This community service activity was carried out by Lecturers of the Nursing and Midwifery Department in cooperation with the students of 2nd Semester of Nursing and Midwifery Department of STIKes Patria Husada Blitar. The activity were held on July 2022. The method used in this activity was a lecture session and question and answer about corrupting behavior in the school environment with leaflet media. The activities was carried out in accordance with the planning of the subject lesson. The activity was carried out on freshman at TKN Bendogerit 1 Blitar City, SDN 02 Plosokerep Kota Blitar, SMPN 1 Sanan Kulon, Blitar Regency and the Ibn Mas'ud Sum Islamic Boarding School Foundation Garum, Blitar Regency with the total number of students was 265 students. The initiation of anti-corruption values must be carried out from an early age, starting from basic education to higher education. planting anti-corruption values in schools can strengthen the character of students, namely the initiation of the value of honesty, concern for others, responsibility, respect for others, discipline, simplicity, and fighting power or persistence in learning.